The goal is attainable: the effects of goal gradient and sub-goals on escalation of commitment in a new product evaluation (INMR - Innovation & Management Review, 2021)
Purpose – The purpose of this study is to investigate whether, in the context of making a go/no-go decisionregarding a failing new product, the use of a stopping rule and/or a new decision-maker would reduce theescalation of commitment (EOC).Design/methodology/approach – This study uses a classroom experiment design and uses logisticregression and a chi-square test to analyze its data.Findings – The findings show that both responsible and non-responsible participants are more likely toperceive the negative performance of a new product as less negative and believe that the goal for the productcan be reached when there is a stopping rule and proximal negative feedback indicates a level of performancebelow but very close to it than when there is no stopping rule. Therefore, they are more likely to continue thefailing new product, whether they are responsible for the product or not. However, non-responsible decisionmakers are more likely than their responsible counterparts to discontinue the failing new product in theabsence of a stopping rule.Research limitations/implications – This paper extends the theory of EOC by showing that the use ofa stopping rule and/or a new decision-maker may not reduce EOC.Practical implications – This paper provides useful guidelines for managers on how to reduce EOC.Originality/value – The originality and value of this paper are found in the investigation of a situation inwhich the use of a stopping rule and/or a new decision-maker may not reduce the EOC.